Flirting in the poetry of Abu Al-Ala Al-Maari: A stylistic study - Almotiry, Omar bin Nooh (Research Journal in Advanced Humanities, 2025)
This study aims to contribute to investigating the facts of the ancient literary heritage and revealing its contents, by returning to the past and recalling it through extrapolating its texts. To reveal its cultural richness and the diversity of its literary purposes for a single poet, and the ways of mixing them and their psychological and social motives. It is to measure the impact of the psychological state on the emotional feelings and strong, sincere emotions that dominated him at that time, the extent of their influence in shaping his images, and his methods of expressing them. In addition to their influence on his reality without limiting it to a specific textual reality, perhaps imposed on him by reflexive circumstances.